BASIC ANXIETY IN JANE AUSTEN’S PRIDE AND PREJUDICE AND EMMA - Djelloul, Hana (PEOPLE: International Journal of Social Sciences, 2024)
This paper examines Jane Austen’s representation of the heroines of Pride and Prejudice and Emma, using Karen Horney’s psychosocial theory of basic anxiety that emphasizes the role of childhood experiences and the impact of socialization on an individual’s psychological development. Firstly, the examination shows certain episodes in the heroines’ early experiences that shape their adult identity and self-knowledge. The analysis reveals that those heroines are highly affected by their parents or chaperones, who themselves may suffer from neurotic problems that impede their ability to properly provide care and support for their children. Moreover, this research delves into how social norms and expectations affect the heroines’ self-image and worldview.